Corporate M&As and Labor Market Concentration: Efficiency Gains or Power Grabs? - CICERO, DAVID; SHEN, MO; SHENOY, JAIDEEP (Journal of Finance, 2026)
ABSTRACT Mergers of firms that share labor markets increase labor market concentration which can lead to labor efficiency gains and/or create labor market power for the merged firms. Using a novel measure based on establishment‐level employment data, we find that merger‐induced increases in labor market concentration explain value creation in a sample of completed U.S. public firm mergers from 1991 to 2016. Analysis of the stock market reactions of rival, supplier, and customer firms, as well as firm‐ and establishment‐level real effects in the merging firms, supports a labor efficiency explanation of these merger gains.